Mechanistic insights into the electrochemical reduction of CO2 to CO on Ni(salphen) complexes - Realista, S. (2023)
LA/P/0056/2020. The NMR spectrometers are part of the National NMR Network (PTNMR) and are partially supported by Infrastructure Project No 022161 (co-financed by FEDER through COMPETE 2020, POCI and PORL and FCT through PIDDAC). FCT is acknowledged for PTDCQUI-QIN0252_2021 (PNM). The CARISMA COST action CM1205 is acknowledged. MJC thanks N. A. G. Bandeira for technical assistance. The CATSUS doctoral programme is also acknowledged. Publisher Copyright: © 2023 The Royal Society of Chemistry.